Detection of ostium secundum atrial septal defects by transoesophageal cross-sectional echocardiography. Issue 4 (April 1983) - Hanrath, P; Schlüter, M; Langenstein, B A; Polster, J; Engel, S; Kremer, P; Krebber, H J
Abstract : Transoesophageal cross-sectional echocardiography has special advantages when investigating the interatrial septum which is imaged perpendicularly without echo dropouts from an oesophageal transducer position. The technique was successfully used in 19 out of 20 patients (95%) with an ostium secundum atrial septal defect and in 30 control subjects. In all of the latter the interatrial septum was visualised as a continuous echo structure separating the atria, whereas a distinct discontinuity representing the septal defect was apparent in all patients with atrial septal defect. Echocardiographic measurement of the defect size correlated well with surgical findings in 11 patients who underwent open heart surgery in the course of this study. In a comparative transthoracic examination, adequate recordings were obtained in 18 of the 20 patients and in 26 of the 30 control subjects. Direct subcostal visualisation of the defect was reliable in 10 of 18 patients. Peripheral venous contrast studies were also performed with the transoesophageal as well as the transthoracic technique. Echo contrast remained confined to the right heart in the control subjects. Left sided contrast appearance diagnostic of an interatrial communication was shown in the patients using the transoesophageal technique (100% sensitivity), with an additional right atrial negative contrast apparent in seven patients. The transthoracic approach, on the other hand, showed left sided echo contrast in 14 of 18 patients and an additional negative contrast effect in two of the 14. It is concluded that transoesophageal is superior to transthoracic cross-sectional echocardiography as a highly sensitive method for the detection and evaluation of ostium secundum atrial septal defects.